The Relationship Between Disability and Variables of Depression, Cognitive Status, and Morale Among Older People - Mohammad Reza Shahbazi; Mahshid Foroughan; Reza Salman Roghani; Mehdi Rahgozar (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: This study aimed to assess disability and its relationship with depression, cognitive status, and morale in older people. Methods & Materials: This descriptive-analytic research was conducted in a day-care rehabilitation center of Kahrizak charity foundation. A total of 90 older adults were selected by total enumeration sampling method. For the evaluation of study participants, we used The World Health Organization Disability Assessment 2.0 (WHODAS II) (36 items). This questionnaire examines the person’s disability in 6 domains of cognition, mobility, self-care, getting along, life activities, and social participation. The depression status was determined by Geriatric Depression Scale (GDS-15), cognitive status by Abbreviated Mental test (AMT), and morale of older people by Lawton’s Philadelphia Geriatric Center Morale Scale. The Chisquare test, Independent t-test, Mann-Whitney U-test, Kruskal-Wallis, and the Spearman correlation coefficient were carried out to analyze the data. Results: The mean (SD) score of older adults’ disability was 20.61 (13.66) indicating a significant difference between men and women (P=0.001). The women’s mean disability score was higher than that of men. With regard to 6 domains of disability, the highest disability was seen in domains of mobility, life activities, and participation. There were also significant differences between men and women with regard to the mean disability scores of mobility (P=0.001), life activities (P=0.001), and participation (P=0.005), i.e., the mean disability scores of women were higher than those of men. However, there were no differences between men and women with regard to domains of getting along, cognition, and self-care. Furthermore, there were no significant differences between various educational groups with regard to mean scores of disabilities. There were significant associations between disability scores and depression (P<0.001), cognitive status (P<0.001), and morale of older people (P<0.001). This association was direct in depression and reverse in cognitive status, and morale, i.e., with an increase in depression scores and a decrease in cognitive status and morale, the disability of older people increases. There were significant and reverse associations between disability and 3 subscales of spirit of agitation (P<0.001), attitudes to aging (P<0.001), and dissatisfaction with loneliness (P<0.001). Conclusion: Disability in older people had a significant relationship with their depression, cognitive status, and morale. Thus, the degree of their disability can be lowered by prevention and early treatment of depression, promotion of memory, delaying cognitive disorders, as well as providing morale enhancement programs, creating a positive attitude toward old age, and increasing life satisfaction in older people.